A Novel Diterpenoid Suppresses Osteoclastogenesis and Promotes Osteogenesis by Inhibiting Ifrd1‐Mediated and IκBα‐Mediated p65 Nuclear Translocation. (21st February 2018) - Xie, Zi'ang; Yu, Hejun; Sun, Xuewu; Tang, Pan; Jie, Zhiwei; Chen, Shuai; Wang, Jiying; Qin, An; Fan, Shunwu
ABSTRACT: Osteoporosis develops because of impaired bone formation and/or excessive bone resorption. Although the pharmacological treatment of osteoporosis has been extensively developed, alternative treatments are still needed. Here, we showed that oridonin (ORI), a diterpenoid isolated from Rabdosia rubescens, can suppress osteoclastogenesis and enhance osteogenesis. ORI inhibited the receptor activator of nuclear factor‐κB (NF‐κB) ligand (RANKL)‐induced osteoclast formation and bone resorption through the inhibition of p65 nuclear translocation. ORI‐induced inhibition of this translocation led to an increase in osteoblast differentiation and mineralization through the promotion of Smad1/Smad5 phosphorylation. Further analyses demonstrated that the inhibition of p65 nuclear translocation is due to the suppression of IκBα phosphorylation and the induced proteasomal degradation of interferon‐related development regulator 1 (Ifrd1), a transcriptional corepressor that is involved in the suppression of NF‐κB nuclear translocation. Moreover, mice treated with ORI at catabolic and anabolic windows showed a considerable attenuation of ovariectomy (OVX)‐induced osteoporosis. Taken together, our findings reveal that ORI protects against OVX‐induced bone loss via inhibiting osteoclastic bone resorption but enhancing osteoblastic bone formation through abolishing both Ifrd1‐mediating and IκBα‐mediated p65 nuclear translocation. These results show the potential of ORI for treatment of osteoporosis and highlight Ifrd1 as a another novel promising target for anti‐osteoporotic drugs. © 2017 American Society for Bone and Mineral Research